2008
DOI: 10.2118/99744-pa
|View full text |Cite
|
Sign up to set email alerts
|

Favorable Attributes of Alkaline-Surfactant-Polymer Flooding

Abstract: A laboratory study of the alkaline-surfactant-polymer (ASP) process was conducted. It was found from phase-behavior studies that for a given synthetic surfactant and crude oil containing naphthenic acids, optimal salinity depends only on the ratio of the moles of soap formed from the acids to the moles of synthetic surfactant present. Adsorption of anionic surfactants on carbonate surfaces is reduced substantially by sodium carbonate, but not by sodium hydroxide. The magnitude of the reduction with sodium carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
124
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(130 citation statements)
references
References 22 publications
6
124
0
Order By: Relevance
“…As stated earlier, surfactant plays a pivotal role in microemulsion formation, and among all surfactants, anionic surfactants are the most well-known and widely used surfactants in oil recovery (Liu et al 2008). The domain of cationic surfactant-based microemulsion methods is still less explored, and this could be a future area of research for scientists targeting enhanced oil recovery from carbonate reservoirs.…”
Section: Alkali-surfactant Floodingmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, surfactant plays a pivotal role in microemulsion formation, and among all surfactants, anionic surfactants are the most well-known and widely used surfactants in oil recovery (Liu et al 2008). The domain of cationic surfactant-based microemulsion methods is still less explored, and this could be a future area of research for scientists targeting enhanced oil recovery from carbonate reservoirs.…”
Section: Alkali-surfactant Floodingmentioning
confidence: 99%
“…ASP for carbonate reservoirs received little focus until the last few years. Reasons include: the high-divalent-ion environment of the carbonate reservoirs leads to the formation of calcium and magnesium sulfonates with the typical commercially available surfactants (alkyl/aryl sulfonates) that either precipitate or partition out into the oil phase (Liu et al 2008). An exception to this observation was reported in the early works of Adams and Schievelbein 1987, who demonstrated that oil could be displaced from a carbonate reservoir using a mixture of petroleum sulfonates and alkyl ether sulfates or alkyl/aryl ether sulfates.…”
Section: Alkali-surfactant-polymer Floodingmentioning
confidence: 99%
“…(2008) has proved that soap-to-surfactant ratio is important, which has significant contribution in order to understand the ASP process [47]. Besides, formation wettability can be altered with the presence of alkali to become more oil-wet or water-wet.…”
Section: Mechanisms Of Alkaline Floodingmentioning
confidence: 99%
“…Liu et al [8] have also reported that the mixture of the surfactants would be able to tolerate hash reservoirs condition with high salinity concentration compared to single surfactant component solution. According to their results considering chemicals with intermediate groups connecting the hydrophobic parts to the hydrophilic sections raises the droplet stability in the micro-emulsion state and provides more stable interfaces.…”
Section: Introductionmentioning
confidence: 99%